Indonesian Jihadists and Syria : training ground? - Arianti, Vidia (2014)
Syria is becoming a “university for jihad education”, a term coined by Indonesian jihadist ideologue and leader of Jamaah Ansharut Tauhid (JAT) Abu Bakar Baasyir, referring to Islamist foreign fighters who continue to flock into Syria. Despite no reports of Indonesians fighting there, the civil war has triggered fundraising activities and extended the international contacts of the Indonesian jihadists.